Respons Biologis Puyuh setelah Pemberian Cahaya Monokromatik: suatu Kajian Kualitas Telur - Mardiati, Siti Muflichatun; Kasiyati, Kasiyati; Irawati, Fika; Silalahi, Adonia B (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
Light schedule is one of improvement in avian culture. The objective of the research was evaluate the potential of monochromatic light used to source artificial light for increased the egg quality. One hundred and twenty quails (Coturnix coturnix japonica) were divided into four treatments of lights, with thirty quails in each treatments. The treatments were red, green, and blue lights with intensity of 15 lux. Control treatment used yellow incandescent bulb of 15 watt. The red, green, and blue lights were provided by light emitting diodes (LED). All lights treatment were given for 14 h daily, started from 17.00 to 07.00. The result showed that quails exposed to monochromatic light significant (P<005) in abdominal fat, the body weight, feed consumption, triglyseride concentration, and the fat content in egg, and the egg weight, without significant effect in the egg protein. Blue light could be used to alternative in quail culture for improve the egg quality